Filtration performance of three models of N95 filtering facepiece respirators following clinical usage and vaporized hydrogen peroxide decontamination. (January 2023) - Cooper, J.; Csapó, A.; Ranasinghe, R.; Jeronimo, M.; Brockington-Tyhy, T.; Alawfi, S.; Wong, T.
Summary: Background: N95 filtering facepiece respirators (FFRs) are essential personal protective equipment (PPE) for protecting healthcare workers from airborne pathogens. Aim: To perform the first large-scale evaluation of particulate filtration efficiency (PFE) of three models of N95 FFRs following clinical usage and vaporized hydrogen peroxide (VHP) decontamination. Methods: Three variables were assessed for effect on PFE following VHP decontamination: VHP sterilizer model, N95 respirator model, and prior N95 clinical usage. Findings: The VHP sterilizer model and N95 FFR model impacted PFE performance. Worn N95 FFRs had a 91% lower odds of exhibiting ≥95% PFE compared with the control. Conclusion: This work highlights the importance of validating any N95 FFR decontamination programme in its entirety, including prior clinical usage.